Analyzing Polysemous Concepts from a Sociological Perspective - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2008)
The article offers a critical examination of the idea of standardization of concepts throughout the newest history of sociological thought. Because of their prior commitments to either universalism or relativism, sociologists have been blind to the possibilities of relationism. It is argued that sociologists must acknowledge the relational nature of definitions and learn to live with this understanding. Although the concepts are not so divergent as is commonly assumed, the significance of the idea of standardization is limited. Certain isolated abstract concepts cannot be evaluated on one-dimensional basis. It is argued that it is necessary to negotiate concepts at a higher level of metatheoretical abstraction. In the construction of the relational scheme, four main paradigmatic views are discernable: macro, micro, conflictual, integrationist.
Keywords: standartization of concepts; relationism; paradigm